Design and measurement of a piezoresistive triaxial accelerometer based on MEMS technology - 杜春晖 何常德 于佳琪 葛晓洋 张永平 张文栋 (Journal of semiconductors, 2012)
With the springing up of the MEMS industry,research on accelerometers is focused on miniaturization, integration,high reliability,and high resolution,and shares extensive application prospects in military and civil fields.Comparing with the traditional single cantilever beam structure or ＂cantilever-mass＂ structure,the proposed structure of ＂8-beams/mass＂ with its varistor completely symmetric distribution in micro-silicon piezoresistive triaxial accelerometer in this paper has a higher axial sensitivity and smaller cross-axis sensitivity.Adopting ANSYS, the process of structural analysis and the manufacturing flow of sensing unit are showed.In dynamic testing conditions, it can be concluded that the axial sensitivity of x,y,and z are Sx-48μV/g,Sy = 54μV/g and Sz = 217μV/g respectively,and the nonlinearities are 0.4%,0.6%and 0.4%.